The investıgatıon of symptoms and therapy delay in children with cancer during COVID pandemic: A center experience - Yilmaz, Yasin; Tanyildiz, Gülşah; Sahin, Sifa; Eryilmaz, Cansu Ceren; Bilici, Mustafa; Karaman, Serap; Tugcu, Deniz; Unuvar, Aysegul; Karakas, Zeynep (Cerrahpaşa Medical Journal, 2023)
Objective: The COVID-19 pandemic had a worldwide effect on people as well as on pediatric patients with cancer. This effect also caused cancer therapy plan alterations. In this study, we aimed to investigate pediatric patients with cancer who were diagnosed as having COVID-19 infections and the alterations in treatment plans. Methods: Pediatric patients with cancer who were followed up in XXX Medical Faculty Pediatric Hematology and Oncology Outpatient Clinic and were diagnosed as having COVID-19 between March 2020 and March 2022 were retrospectively analyzed. Results: A total of 28 patients were diagnosed as having a COVID-19 infection. Forty-three percent of the patients had leukemia, and 57% had solid tumors. More than half (58%) of the patients had mild COVID-19 symptoms. Sixteen (57%) patients had a therapy delay because of COVID-19 infections. The mean therapy delay day was 5.8 ± 2.9 (median: 5 days). Hematologic malignancy (leukemia) had a delay rate of 33% in therapy, and it was 75% in solid tumors. Conclusion: The COVID-19 pandemic affected all people as well as pediatric patients with cancer. The rate of delay in therapy was 57% in our overall pediatric cancer population. The prevention of patients against virus, vaccination of parents, and review of therapy plans might be scheduled in cancer centers.